(3fXGe GdGJUGd h GdEYdGe GdOhdj (B:s (3GdVHW h GdSjQI (B/s - (3GdLeGd, QGSe eMeOs ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2005)
(3dbO CUHM GdGJUGd h GdEYdGe GdOhdj eVeGQ SHGb Hjf Gdbhi GdcHQi HGYJHGQg eaJGMG aeGdG dVeGf GdSjWQI h GdgjefI(B.. (3h ef Ke HGJJ GdJWhQGJ GdMGOKI aj gPG GdeVeGQ eMd GgJeGe gPg Gdbhi (B.. (3Hd h JLGhRGJgG Gdi chfgG GMO GdechfGJ GdGSGSjI aj GdfXGe GdGbJUGOj GdOhdjs
(3HHdjhZQGajG (B: (3U(B.185-194s
Keywords: (3GdGJUGd (B, (3GdEYdGe GdOhdjs